Desiccation of sediments affects assimilate transport within aquatic plants and carbon transfer to microorganisms. (11th August 2016) - von Rein, I.; Kayler, Z. E.; Premke, K.; Gessler, A.
Abstract: With the projected increase in drought duration and intensity in future, small water bodies, and especially the terrestrial–aquatic interfaces, will be subjected to longer dry periods with desiccation of the sediment. Drought effects on the plant–sediment microorganism carbon continuum may disrupt the tight linkage between plants and microbes which governs sediment carbon and nutrient cycling, thus having a potential negative impact on carbon sequestration of small freshwater ecosystems. However, research on drought effects on the plant–sediment carbon transfer in aquatic ecosystems is scarce. We therefore exposed two emergent aquatic macrophytes, Phragmites australis and Typha latifolia, to a month‐long summer drought in a mesocosm experiment. We followed the fate of carbon from leaves to sediment microbial communities with 13 CO2 pulse labelling and microbial phospholipid‐derived fatty acid (PLFA) analysis. We found that drought reduced the total amount of carbon allocated to stem tissues but did not delay the transport. We also observed an increase in accumulation of 13 C‐labelled sugars in roots and found a reduced incorporation of 13 C into the PLFAs of sediment microorganisms. Drought induced a switch in plant carbon allocation priorities, where stems received less new assimilates leading to reduced starch reserves whilst roots were prioritised with new assimilates, suggesting their use for osmoregulation. There were indications that the reduced carbon transfer from roots to microorganisms was due to the reduction of microbial activity via direct drought effects rather than to a decrease in root exudation or exudate availability.